Levantamento de patologias causadas por infiltrações devido à falha ou ausência de impermeabilização em construções residenciais na cidade de Campo Mourão – PR - Hussein, Jasmim Sadika Mohamed (2013)
This study aims to examine some of the causes of the problems related to waterproofing, the pathologies that can arise due to these problems and some suggestions for how to fix them. In the city of Campo Mourao, some samples were surveyed who have certain kinds of diseases, possibly caused by the lack of waterproofing or error in its execution where it was noted that this process is hardly done correctly or with the products listed, making it difficult repair them, as they leave the products are exchanged and preventive services, for correction, causing rework and additional costs to the owners of the residences. To ensure the economic viability and durability of construction, it is necessary to consider the project as proof of a work, which products to use, and which locations are performing this important service.